O‘qituvchi kompetentligini takomillashuvida kvalifikatsiya va kompetentsiya (xususiy va tayanch kompetentsiyalar) - Nazarova, Z.T (SCIENCE and SOCIETY, 2021)
The article provides information on some issues of the development of special and basic competencies in improving the pedagogical activity of teachers of the subject «Upbringing».
Keywords: qualifications; competencies; social activity; creativity; personal competence; spiritual and moral qualities